Ineransi Alkitab sebagai Dasar Kurikulum Pendididikan Kristen - Hardi Budiyana (Jurnal Teologi Berita Hidup, 2021)
Inerrancy means the Bible is infallible. Because the Bible was revealed by God the Holy Spirit Himself. Even though the researcher is a sinner; however, the initiator is a God who cannot do wrong. The Holy Spirit uses all the individual potentials (shortcomings and strengths) of the Bible writers and is completely under the leadership and control of the Holy Spirit, so that what the authors of the books of the Bible write do not come from the author, but from God concerning the Word of God himself. A Christian can accept this inerrant biblical quality, so he must also accept other biblical qualities. This study uses a descriptive qualitative method regarding the Christian education curriculum that must be based on the inerrancy of the Bible. Biblical inerrancy emphasizes that the Bible is the Word of God, the Bible was written without errors because the idea of writing came from God. The curriculum is structured based on the inerrancy of the Bible with the aim of Christian education so that learners know God's work of salvation in and through the Lord Jesus alone, so that they believe that Jesus is God, so that those who believe have eternal life and their lives are changed by the Holy Spirit through the power of the Bible. The power of the Bible is because the Bible is the Word of God. Nothing can survive under the sovereignty of God's written Word, which is the Bible. Therefore, the Christian religious education curriculum is built based on the Bible in order to achieve its goals.Ineransi berarti Alkitab tidak mungkin salah. Karena Alkitab diwahyukan oleh Allah Roh Kudus sendiri. Walau penelitinya adalah orang berdosa; namun, inisiatornya adalah Allah yang tidak mungkin berbuat salah. Roh Kudus menggunakan semua potensi individual (kekurangan dan kelebihan) penulis Alkitab dan secara utuh berada dalam pimpinan dan kontrol Roh Kudus, sehingga yang ditulis oleh penulis kitab dalam Alkitab bukanlah berasal dari penulis, melainkan dari Allah mengenai Firman Allah sendiri. Orang Kristen dapat menerima sifat Alkitab yang ineransi ini, maka ia pasti juga menerima sifat-sifat Alkitab yang lain. Penelitian ini menggunakan metode kualitatif deskriptif mengenai kurikulum pendidikan  Kristen harus didasarkan pada ineransi Alkitab.  Ineransi Alkitab menekankan Alkitab adalah Firman Tuhan, Alkitab ditulis tanpa ada kesalahan karena ide dari tulisan berasal dari Allah. Kurikulum disusun berdasar pada ineransi Alkitab dengan tujuan Pendidikan Kristen agar pembelajar mengenal karya keselamatan Allah di dalam dan melalui Tuhan Yesus saja, supaya percaya bahwa Yesuslah Allah, sehingga yang percaya beroleh hidup yang kekal dan hidupnya diubah oleh Roh Kudus melalui kuasa Alkitab. Kuasa Alkitab adalah karena Alkitab adalah Firman Allah. Tidak ada yang dapat bertahan di bawah kedaulatan Firman Tuhan yang tertulis, yaitu Alkitab. Karena itu kurikulum pendidikan Agama Kristen dibangun berdasarkan Alkitab agar mencapai tujuan.